Muscle Strength and Size Balances between Reciprocal Muscle Groups in the Thigh and Lower Leg for Young Men - Akagi, R.; Tohdoh, Y.; Takahashi, H. (International Journal of Sports Medicine, 2012)
The present study investigated whether the muscle size balance affects the muscle strength balance between reciprocal muscle groups in the thigh and lower leg. 18 young men volunteered as subjects. The joint torques developed during isometric maximal voluntary knee extension and flexion, plantar flexion and dorsiflexion were measured using a dynamometer. The muscle volumes of knee extensors and flexors, plantar flexors and dorsiflexors were determined by magnetic resonance imaging. For each of the muscle groups, the joint torque was significantly correlated with the muscle volume (r=0.644–0.847) and the y-intercept of the regression line between them was not significantly different from zero. Based on these observations, the dependencies of muscle strength balance on muscle size balance between the knee extensors and flexors and between the plantar flexors and dorsiflexors were investigated using the joint torque and muscle volume. The correlation between muscle volume ratio and joint torque ratio was significant between the plantar flexors and dorsiflexors (r=0.622) but not between the knee extensors and flexors (r=0.128). Thus, it is suggested that the strength balance is strongly affected by the size balance between the reciprocal muscle groups in the lower leg but not in the thigh.
Keywords: joint torque; muscle volume; knee extensors; knee flexors; plantar flexors; dorsiflexors